Diseminasi pengetahuan dalam penilaian berasaskan sekolah dalam kalangan guru - Dayangku Nur Hazila, bt Awg Ja'afari (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was conducted to investigate the dissemination of knowledge in School Based Assesment among teachers. Among the apects examined in this study are the types of knowledge disseminated among the teachers, the way knowledge is disseminated, the weakness of knowledge dissemination, as well as measures to address the problem of dissemination of knowledge in School Based Assesment. The study involved a total of ten informants who were selected through purposive sampling. The study found out that the dissemination of knowledge in School Based Assesment can assist in improving the skills and knowledge of teachers in performing their duties. It is hoped that, the information obtained will be used as a guideline for further studies in the future.